Computational analysis of two-phase flow and heat transfer in parallel and counter flow double-pipe evaporators. (January 2017) - Abishek, S.; King, Andrew J.C.; Narayanaswamy, Ramesh
Highlights: Two phase flow and heat transfer in double pipe evaporator is studied computationally. Eulerian two-fluid framework in conjunction with RPI wall-boiling model is validated. Relatively greater vapor generation upstream benefits parallel flow configuration. Flow of FC-72 in the tube-side results in higher vapor generation for cases studied. Net heat transfer effectiveness of parallel flow is about 6% higher than counter flow. Abstract: A computational study is carried out to compare the two-phase flow and heat transfer characteristics of a double-pipe evaporator operating under parallel and counter flow configurations for use in waste heat recovery and low grade geothermal applications. The heat exchanger considered uses low boiling point fluid FC-72 to recover thermal energy from water that is at a temperature greater than the boiling point of FC-72 through forced convective boiling. The simulations are carried out at steady state using the SST- k - ω Reynolds-Averaged-Navier-Stokes equations, and by employing the Eulerian two-fluid formulation for the region of the heat exchanger where multiphase flow with phase-change occurs. The net heat flux from the wall during nucleate boiling is evaluated using the Rensselaer Polytechnic Institute wall heat flux partitioning model with appropriate empirical and mechanistic closures for the underlying physical mechanisms such as ebullition characteristics. The present computational methodology is extensively validated by comparison of the predicted fluid and wall temperatures, local vapor fractions and heat transfer coefficients against experimental data in the literature. For the range of parameters considered, contrary to that generally expected in single phase double-pipe heat exchangers, under two-phase conditions (boiling), the parallel flow configuration is found to result in a greater thermal effectiveness as compared to the counter flow. This is observed irrespective of whether FC-72 flows in the tube or annulus, and can be attributed to the greater vapor generation relatively upstream and for most of the length of the heat exchanger during parallel flow conditions. For the heat exchanger considered, the net FC-72 vapor generation is also greater when FC-72 flows in the tube-side as compared to that in the annulus under both parallel and counter flow configurations, although with marginal variation in the overall heat transfer rates.